CUSTOMER CREATION, EMPLOYEE PROACTIVENESS AND BUSINESS SURVIVAL IN COMPETITIVE MARKET ENVIRONMENT OF LAGOS STATE, NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
The study examined customer creation, employee proactiveness and business survival in competitive market environment of Lagos State, Nigeria. Three hypotheses were tested in this study. The descriptive research design of survey was used. The population of the study comprised 11,463 Businesses (SMEs) who have employees of 5-55 and registered with the Small and Medium Enterprises Development Agency of Nigeria (SMEDAN). The sample size is 386 businesses using Taro Yamene formula. The study used researchers self-developed instrument title: Customer’s Creation, Employee Proactiveness and Businesses Survival Questionnaire (CCEPNSQ) with reliability coefficient (r = .93) for data collection. Inferential statistics of Pearson Product Moment Correlation (PPMC) was used for testing hypotheses 1 and 2 while hypothesis 3 was tested using multiple regression analysis. The findings of the study showed that there was positive significant relationship between customer’s creation (r = 0.317, p
Keywords: Customer’s Creation; Employee Proactiveness; Businesses Survival